Prevention of musculoskeletal injuries in informal caregivers of dependent patients at home - Maria João Matos; Clara Araújo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Providing care to the person with dependence can be extremely difficult and exhausting at various levels, where the overload inherent to the patient's manual movement, may cause poor posture and consequently musculoskeletal injuries, in the informal caregiver. Musculoskeletal injuries, when considered a multifactorial health problem, become a priority for Rehabilitation Nursing, where informal caregivers of dependent patients at home deserve special attention. This research aimed to train informal caregivers of dependent patients at home, to apply preventive measures for musculoskeletal injuries, inherent to the manual movement of dependent patients, at home. Methodology: project methodology. The situation diagnosis was made through a structured interview. For the observation of the application of preventive measures for musculoskeletal injuries, a behavior observation grid with twenty items was applied, before and after the completion of two theoretical-practical training on preventive procedures for musculoskeletal injuries, in the context care delivery Results: The sample for this study consisted of ten informal caregivers. All participants were female, with an average age of 53 years; 80% had no musculoskeletal symptoms before starting to care; 100% did not avoid sudden efforts, nor the use of the back muscles and did not perform stretching exercises. After sessions, there was an improvement in relation to fifteen of the twenty items observed. Conclusion: This study highlights the relevance of the Rehabilitation Nursing intervention, in the training of informal caregivers of dependent patients at home, in the prevention of injuries to the musculoskeletal system.